Diabetes Care During COVID-19 Pandemic in Singapore Using a Telehealth Strategy - Lian, Xia; Dalan, Rinkoo; Seow, Cherng Jye; Liew, Huiling; Jong, Michelle; Chew, Daniel; Lim, Brenda; Lin, Anita; Goh, Eunice; Goh, Christina; Othman, Noorani Bte; Tan, Lucy; Boehm, Bernhard O. (Hormone and Metabolic Research, 2021)
Singapore currently has one of highest number of confirmed COVID-19 cases in Southeast Asia. To curb the further spread of COVID-19, Singapore government announced a temporary nationwide lockdown (circuit breaker). In view of restrictions of patients’ mobility and the enforcement of safe distancing measures, usual in-person visits were discouraged. Here we describe how diabetes care delivery was ad hoc redesigned applying a telehealth strategy. We describe a retrospective assessment of subjects with diabetes, with and without COVID-19 infection, during the circuit breaker period of 7th April to 1st June 2020 managed through Tan Tock Seng Hospital’s telehealth platform. The virtual health applications consisted of telephone consultations, video telehealth visits via smartphones, and remote patient monitoring. The TTSH team intensively managed 298 diabetes patients using a telehealth strategy. The group comprised of (1) 84 inpatient COVID-19 patients with diabetes who received virtual diabetes education and blood glucose management during their hospitalisation and follow-up via phone calls after discharge and (2) 214 (n=192 non-COVID; n=22 COVID-positive) outpatient subjects with suboptimal glycaemic control who received intensive diabetes care through telehealth approaches. Remote continuous glucose monitoring was applied in 80 patients to facilitate treatment adjustment and hypoglycaemia prevention. The COVID-19 pandemic situation mooted an immediate disruptive transformation of healthcare processes. Virtual health applications were found to be safe, effective and efficient to replace current in-person visits.
Keywords: COVID-19; virtual diabetes education; telehealth strategy; circuit breaker